2011
DOI: 10.12659/msm.881806
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency haplotypes of E-selectin polymorphisms G2692A and C1901T give increased protection from coronary artery disease

Abstract: SummaryBackgroundE-selectin polymorphisms are an independent atherosclerosis and coronary artery disease (CAD) risk factor. This study aimed to investigate the link between the C1901T and G2692A E-selectin tagging SNPs and their haplotypes and the extent of coronary artery disease in Polish patients.Material/MethodsFor this study 321 patients were recruited CAD extent by coronary angiography and E selectin gene variant were investigated using HapMap, PCR/RFLP, multivariate logistic regression and haplotype ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recently, results from a meta-analysis reported that the SELE gene A561C polymorphism was significantly associated with susceptibility to ischemic stroke, which results from cerebrovascular atherosclerosis [57] . Several polymorphisms in the SELE gene, such as A561C [32] , G98T [35] , L554F [20] , G2692A and C1091T [58] , were successively reported to be associated with atherosclerosis and CAD. Sarecka-Hujar et al suggested that the two SNPs of the SELE gene, A561C and G98T, were likely to control the SELE expression [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, results from a meta-analysis reported that the SELE gene A561C polymorphism was significantly associated with susceptibility to ischemic stroke, which results from cerebrovascular atherosclerosis [57] . Several polymorphisms in the SELE gene, such as A561C [32] , G98T [35] , L554F [20] , G2692A and C1091T [58] , were successively reported to be associated with atherosclerosis and CAD. Sarecka-Hujar et al suggested that the two SNPs of the SELE gene, A561C and G98T, were likely to control the SELE expression [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies in a German population showed possible associations between the S128R and L554F variations of the E-selectin gene and severe atherosclerosis, hypertension and cerebrovascular diseases (12,13). However, the low frequency haplotypes of E-selectin polymorphisms G2692A and C1901T is currently considered to be protective for coronary artery disease (14). Additionally, the association between SELE SNPs and the E-selectin level remains controversial (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%